Comparison of Patient Profiles of Ventilator-Associated Pneumonia versus Non-Ventilator Associated Pneumonia in Children from Rawalpindi - Mehmood, Danial; Hassan, Shamama; Tabussam, Samina; Akhlaq, Bilal; Ali, Haider; Malik, Sumbal (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study paediatric patient profiles for comparing demographic and clinical variables between ventilator-associated pneumonia patients and non-ventilator-associated pneumonia patients. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Paediatrics, Combined Military Hospital, Rawalpindi Pakistan, from Feb to Jul 2024. Methodology: This study included 200 patients aged between 1 month and 15 years who were divided into two groups: Group-A, containing patients diagnosed with ventilator-associated pneumonia (VAP), based on clinical, radiological, and microbiological findings after experiencing more than 48 hours of mechanical ventilation, and Group-B, which included patients not having ventilator-associated pneumonia (non-VAP) after being ventilated for more than 48 hours. Demographic and clinical variables involved duration of paediatric intensive care unit (PICU) stay, body temperature, total leukocyte count (TLC), duration of antibiotic use, frequency of sepsis, shock, altered sensorium, and mortality. Results: The mean duration of PICU stay (11.12±2.60 days), mean core body temperature (99.35±1.40°C), mean TLC (19.45±2.79 × 10⁹/L), mean duration of antibiotic use (8.14±0.91 days), frequency of sepsis and shock (37% & 13%), altered sensorium (8%), steroid use (35%), and mortality (20%) were significantly higher (p<0.05) in Group-A than in Group-B patients. Conclusion: Ventilator-associated pneumonia patients exhibited significantly higher illness severity and mortality, which highlighted the need for vigilant monitoring and early intervention.